Some more properties onsemipre- Regular Space(SP- - Suhad K.Hameed, Shahad Jasim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The aim of this research is to give more properties for the semipre-regular topological space which introduced byGovindappa Navalagi[1]. The property of weakly semipre- Hausdorff was considered and the relationamong(SP-